A conditioning platform based on fludarabine, busulfan, and 2 days of rabbit antithymocyte globulin results in promising results in patients undergoing allogeneic transplantation from both matched and mismatched unrelated donor. Issue 1 (January 2014) - Devillier, Raynier; Fürst, Sabine; Crocchiolo, Roberto; El‐Cheikh, Jean; Castagna, Luca; Harbi, Samia; Granata, Angela; D'Incan, Evelyne; Coso, Diane; Chabannon, Christian; Picard, Christophe; Etienne, Anne; et al.
<x xml:space="preserve">Abstract</x> Conditioning regimen including fludarabine, intravenous busulfan (Bx), and 5 mg/kg total dose of rabbit antithymocyte globulin (r‐ATG) (FBx‐ATG) results in low incidence of graft‐versus‐host disease (GVHD) and non‐relapse mortality (NRM) after allogeneic hematopoietic stem cell transplantation (Allo‐HSCT) from HLA‐matched related or unrelated donors (MUD). However, whether this platform produces similar results in the setting of one mismatch unrelated donor (MMUD) Allo‐HSCT is not known. We retrospectively analyzed patients aged less than 65 years who were diagnosed with hematological malignancies and received FBx‐ATG regimen prior to Allo‐HSCT from MUD (N = 74) or MMUD (N = 40). We compared outcome of MUD versus MMUD patients. There was no difference in the cumulative incidence of grades II–IV acute GVHD (MUD: 34% vs. MMUD: 35%, P = 0.918), but MMUD patients developed more grade III–IV acute GVHD (MUD: 5% vs. MMUD: 15%, P = 0.016). The cumulative incidences of overall chronic GVHD (MUD: 33% vs. MMUD: 22%, P = 0.088) and extensive chronic GVHD (MUD: 20% vs. MMUD: 19%, P = 0.594) were comparable. One‐year NRM was similar in both groups (MUD: 16% vs. MMUD: 14%, P = 0.292); similarly, progression‐free survival (MUD: 59% vs. MMUD: 55%, P = 0.476) and overall survival (MUD: 63% vs. MMUD: 61%, P = 0.762) were not different between both groups. With a median follow up of 24 months, 35 of 74 MUD patients (47%) and 19 of 40 MMUD patients (48%) were free of both disease progression and immunosuppressive treatment. We conclude that the FBx‐ATG regimen results in low incidences of NRM and GVHD in both MUD and the MMUD recipients. Am. J. Hematol. 89:83–87, 2014. © 2013 Wiley Periodicals, Inc.